A Novel Stimuli-Responsive Magnetite Nanocomposite as De Novo Drug Delivery System. Issue 4 (4th March 2019) - Mozafari, Zahra; Massoumi, Bakhshali; Jaymand, Mehdi
ABSTRACT: A novel stimuli-responsive magnetite nanocomposite as de novo drug delivery system for cancer chemotherapy is developed successfully through the incorporation of magnetite nanoparticles into PEG- b -(PNIPAAm- b -PAA)2 copolymer. The chemical structures of samples were characterized using FTIR and 1 H NMR spectroscopies. Furthermore, thermal property, morphology, size, and magnetic properties of the nanocomposite were investigated. The DOX loading and encapsulation efficiencies as well as stimuli-responsive drug release ability of the nanosystem were studied. As results, at pH 5.3 and temperature of 41°C the nanocomposite exhibited higher drug release values, which qualified it for cancer chemotherapy according to especial features of cancerous tissue. GRAPHICAL ABSTRACT: